INTEGRATED DISEASE CONTROL STRATEGIES FOR TUBERCULOSIS IN BOVINE POPULATIONS: A MEDICAL APPROACH TO ERADICATION (The Research of Medical Science Review, 2025)
Bovine tuberculosis (bTB), caused by Mycobacterium bovis, remains a persistent zoonotic threat with profound implications for animal health, agricultural productivity, and public health. This study investigates integrated disease control strategies for bTB, emphasizing the synergistic role of diagnostics, vaccination, biosecurity, and veterinary infrastructure. Results indicate that while traditional diagnostic methods like the tuberculin skin test continue to dominate field use, newer modalities such as interferon-gamma assays and PCR provide superior accuracy and early detection capability. Vaccine efficacy analysis revealed that subunit and viral-vectored vaccines demonstrate stronger immunogenic responses and greater diagnostic compatibility than the widely used BCG vaccine. Implementation of stringent biosecurity measures—particularly quarantine, hygiene maintenance, and wildlife fencing—emerged as effective tools for reducing intra- and inter-herd transmission risk. In addition, a survey on the status of health enhancement initiatives underlined the necessity of enhancing the density and quality of laboratories, as well as increasing personnel education and community involvement to maintain eradication initiatives. Studies to this effect confirmed declining bTB incidence rates in regions where the integrated strategies were employed, but enhanced by predictive analysis for resource allocation. However, some challenges still remain owing to wildlife reservoirs, socio-economic davances and dynamics around the world regarding zoonotic diseases transmission. The implications therefore point to the importance of a One Health approach using medical advancement, ecological understanding, and policy frameworks. In conclusion, the study confirms that it is possible to achieve eradication if the measures are maintained, and if the process is continually adapted and done in collaboration with departments and organizations in the specific country and area.